Transfusion of Blood Products in the Postoperative of Cardiac Surgery - Moraes,Antonieta (2021)
Abstract Background: The indiscriminate use of blood transfusion in surgery has been associated with increased risk of infection and increased length of hospital stay. Objective: To identify the average amount of bleeding and rates of transfusion of blood products in the postoperative period of patients undergoing cardiac surgery in a cardiology center. Methods: Medical records of patients who underwent myocardial revascularization surgery and/or heart valve replacement with use of cardiopulmonary bypass (CPB) were analyzed. Perioperative data such as CPB time, hematocrit and hemoglobin values were collected after surgery. The amount of bleeding (mL), blood transfusion (IU), clinical complications and time of hospitalization were also recorded. The correlation between bleeding in the postoperative period and blood transfusion was performed using the Spearman correlation. A p < 0.05 was considered statistically significant. Results: A total of 423 patients undergoing coronary artery bypass grafting (51.5%) or heart valve replacement (33.6%) were included. During the first 24 hours, the average bleeding volume was 353.3 ± 268.3 mL. Transfusion of blood products was required in 40.1% of cases, most frequently (70.6%) in the immediate postoperative period. Red blood cell concentrate was the most frequently used product (22.9% and 60%). Conclusion: The occurrence of bleeding in the cases was low, and when transfusion of blood components was indicated, red blood cell concentrates were the most widely used component. (Int J Cardiovasc Sci. 2021; [online].ahead print, PP.0-0)